Did Germinal Centers evolve under differential effects of diversity vs affinity? - Faro, J. (2010)
The classical view on the process of mutation and affinity maturation that occurs in GCs assumes that their major role is to generate high affinity levels of serum Abs, as well as a dominant pool of high affinity memory B cells, through a very efficient selection process. Here we present a model that considers different types of structures where a mutation selection process occurs, with the aim at discussing the evolution of Germinal Center reactions. Based on the results of this model, we suggest that in addition to affinity maturation, the diversity generated during the GC reaction may have also been important in the evolution towards the presently observed highly organized structure of GC in higher vertebrates.